Public Health Microbiome Curriculum: Looking Below the Tip of the Iceberg for Approaches to Population Health - Melissa K. Melby; Swapna Mylabathula; Meghan B. Azad; Sarah Turner; Naama Geva‐Zatorsky; Carolina Tropini; Melissa B. Manus; Martin Blaser; Mark Nichter (Microbial Biotechnology)
ABSTRACT We discuss the opportunity for public health microbiome curricula to bridge the gaps in knowledge that exist between microbiome researchers and the lay public. We propose equipping public health professionals, important facilitators of public outreach and behaviour change, with three public health curriculum modules focused on breastfeeding, antibiotics and diet. These modules shift the focus from microbes as pathogens to potential partners in promoting health across the life course. Current public health messages cover only the ‘tip of the iceberg’ in exploring mechanisms, and this microbiome curriculum dives below the surface to provide fresh perspectives. These microbiome insights allow us to move beyond a focus on microbes as pathogens to understand the numerous collaborative roles played by the microbiome in producing health, and the upstream factors influencing the microbiome, thereby offering mechanistic insights that can be harnessed for public health education.